A comparison of global governance across sectors: Global health, trade, and multilateral development finance - Matthias Helble; Zulfiqar Ali; Jera Lego (Asian Development Bank Institute (ADBI), 2018)
To what extent do the World Health Organization, the World Trade Organization, and the World Bank remain central today and how much influence do they still wield in shaping the global agenda? While several studies have traced the development of various intergovernmental organizations (IGOs), charting their growth and influence in international affairs, and assessing their prospects, few if any have compared IGOs across various fields. This paper aims to fill this gap by taking a closer look at three different policy fields to better understand the current architecture of global governance, the centrality of IGOs, the role of new and other actors, as well as the strengths and weaknesses of this "new" architecture. The authors find that, first, the emergence of new private players has significantly eroded the centrality of IGOs such that the course of global governance in health, trade, and development finance has changed irreversibly. Second, regional arrangements have overtaken global ones and nonstate actors have assumed more prominent roles. Third, this multiplicity of powerful players has led to some positive outcomes but also greater inefficiencies and redundancies. Fourth, developed countries have been pivotal in eroding the centrality of IGOs, but developing countries are taking on a greater role in global governance. Fifth, the new architecture can be described as one of diversification in global health governance, fragmentation in global trade, and variation in multilateral development finance. Global governance in the 21st century is thus characterized by a proliferation of actors and a decentralization of authority, an erosion of IGO centrality accompanied by a greater role for nonstate actors, developing countries, and by increased regionalism. Depending on the sector of governance, its inherent aims, and the nature of the actors involved, the new architecture may be one of variation, fragmentation, or diversification. While this new architecture is complex and might possibly lead to inefficiencies and redundancies, it allows a greater number of actors to participate, making it more representative of the current world order and making it possible to mobilize more resources to promote development.
Keywords: F13; F53; F55; P45; 330; global development; global governance; global health; global trade; multilateral development banks; public-private partnerships; regional cooperation